ANALISIS PENGARUH PENGETAHUAN PERPAJAKAN, PERSEPSI TENTANG KONSULTAN PAJAK, DAN PERSEPSI TENTANG ACCOUNT REPRESENTATIVE TERHADAP MINAT DALAM MENGGUNAKAN JASA KONSULTAN PAJAK PADA WAJIB PAJAK BADAN DI KPP PRATAMA BANTUL - Fadheil Wiza Munabari; Andri Waskita Aji (Jurnal Akuntansi, 2014)
This study aims to analyze the factors that affect the corporate taxpayers use tax consultant services. The independen variable in this research are knowledge of taxation, perception about tax consultant, and perception about account representative (AR) while the dependent variables is interest in using the services of a tax consultant. The data used in this research is primary data by using a questionnaire. The sampling technique is using purposive sampling. The subject of this research is corporate taxpayers registered In KPP Pratama Bantul by taking sample of 100 respondents. Respondent's answer in the questionnaire were analyzed using linear regression analysis using SPSS 19.00 for then be concluded. Based on the results of the data analysis, found that the tax knowledge of corporate taxpayer and perception abut tax consultant has a positive and significant effect on corporate taxpayer's interest of using tax consultant services. While perception about AR has not effect at all on the corporate taxpayer interest of using services of tax consultant. Keywords: tax knowledges, perception, tax consultants, account representative, interest, tax consultant services, corporate taxpayers